Quasi steady state of nucleate boiling heat transfer in low concentration of single and hybrid Al2O3-SiO2 water-based nanofluids - M. A. H., Aizzat; Muhamad Zuhairi, Sulaiman; Okawa, T. (IOP Publishing, 2020)
Experiment were carried out to clarify the steady state condition of heat transfer coefficient (HTC) for single and hybrid Al2O3-SiO2 water-based nanofluids in low concentration of nucleate pool boiling. Al2O3 and SiO2 were chosen and ultra-sonification for 1 hour after being diluted in distilled water. The total of 0.001 vol.% concentration was divided into composition ratio of 0:100, 25:72, 50:50, 75:25, 100:0 for hybrid nanofluids. Successively, all the HTC values were collected through experimental works. In the present work, it was found that the steady stated for single and hybrid nanofluids were achieved except for single SiO2 nanofluid where even after 5 hours, the value of its ΔTW keep on decreasing. The nanoparticles deposited on the surface heater were suspected as the main factor for the current experimental results.